2019
DOI: 10.1177/1363459319846939
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of diagnosis, stigma, culpability and disclosure in male patients with hepatitis C virus: An interpretative phenomenological analysis

Abstract: The current study aimed to explore the lived experience of patients with HCV infection. Semi-structured interviews were conducted with seven male participants living with HCV and were analysed using Interpretative Phenomenological Analysis (IPA). Two master themes were identified: (1) Diagnosis and the search for meaning, and (2) Impact of stigma on disclosure. Participants reported fears of contaminating others, feelings of stigma and concerns of disclosing the condition to others. Response to diagnosis, stig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Like in other patients with chronic digestive illness, 15,27,28 unsolicited advice regarding diet and exercise was common and experienced as blaming the individual for their symptoms. Blame is a pervasive theme among stigmatized illness, including hepatitis C, 33 lung cancer, 34 and HIV/AIDS 35,36 . At present, the literature on dietary management of gastroparesis is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Like in other patients with chronic digestive illness, 15,27,28 unsolicited advice regarding diet and exercise was common and experienced as blaming the individual for their symptoms. Blame is a pervasive theme among stigmatized illness, including hepatitis C, 33 lung cancer, 34 and HIV/AIDS 35,36 . At present, the literature on dietary management of gastroparesis is limited.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, depression and anxiety were independently associated with stigma, when the model was adjusted for age, sex, marital status, and job. Based on previous studies, aspects of perceived stigma include social rejection, isolation, occupational insecurity, and internalized shame, which are predictors of low self-worth, which can increase anxiety and depression, and reduce adaptation to the disease [40][41][42]. The results of previous studies showed that people with chronic diseases, such as AIDS and lung cancer, experience a relatively high level of stigma which is significantly associated with psychological disorders, such as anxiety and depression [33,[43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…Of the studies, three studies met seven out of 10 of the qualitative critical appraisal criteria (Harris et al, 2014(Harris et al, , 2016Krzeczkowska et al, 2021). All studies scored "Yes" on their congruity between their qualitative methodology and chosen method of data collection, analysis of data, and interpretation of the findings, whereas none of the authors described their influence on the research, and vice-versa.…”
Section: Critical Appraisalmentioning
confidence: 99%
“…The included studies were published from 2014 to 2021 and were conducted in Australia (Rance et al, 2017), United Kingdom (UK) (Harris et al, 2014(Harris et al, , 2016Krzeczkowska et al, 2021), and United States (US) (Barocas et al, 2014;Skeer et al, 2018). Qualitative methodology (Harris et al, 2014(Harris et al, , 2016Krzeczkowska et al, 2021;Rance et al, 2017; (Barocas et al, 2014) were used. Interviews were conducted in all articles and a survey was also undertaken in the mixed-methods article by Barocas et al (2014).…”
Section: Study Characteristicsmentioning
confidence: 99%